ACCESSORY MITRAL VALVE TISSUE CAUSING FEATURES OF LEFT VENTRICULAR OUTFLOW TRACT OBSTRUCTION-A CASE REPORT AND UPDATED LITERATURE REVIEW - Al-Atta, Ayman; Khan, Habib; Sosin, Michael (Journal of Ayub Medical College Abbottabad, 2019)
Accessory mitral valve tissue is a rare congenital anomaly that is commonly incidentally diagnosed. When symptomatic, it tends to present with features of left ventricular outflow (LVOT) obstruction in about two thirds of cases. It is also commonly associated with other congenital anomalies, notably ventricular septal defects. Transthoracic echocardiography is a very useful diagnostic test to make a diagnosis and its widespread use will increase detection of this condition. We are presenting a case of a 29-year-old lady who presented with breathlessness in the third trimester of pregnancy and was subsequently found to have evidence of accessory mitral valve tissue on echocardiography. Keywords: Accessory mitral valve; outflow obstruction